2021 THE YEAR IN LEADERSHIP: The Stories of Faith, Athletics, Business, and Life Which Inspired Us All - Brian Dodd (Maitland Xulon press, 2022)
Do you feel ill-equipped to handle the leadership challenges of a pandemic and post-pandemic world? If so, you no longer have to. In 2021, author, speaker, consultant, and podcaster Brian Dodd helped equip countless leaders across world through his content. Over 80 of his most popular articles make up the pages of 2021- The Year In Leadership: The Stories of Faith, Athletics, Business, and Life Which Inspired Us All. Each chapter is filled with wisdom and insights from the leaders who succeeded and struggled during 2021. Brian takes these lessons from all walks of life and gives you practical steps on how to best use them in your own leadership. As you will discover, the stories are entertaining, challenging, inspiring, and sometimes even sobering. The best leaders are the ones who sense and seize opportunity in the midst of chaos. Brian thinks this describes you. This is why this book was written. By learning the lessons from 2021, it helps ensure you have the potential to become the leader God meant for you to be in 2022.
Includes Bibliography
Keywords: Leadership